Revisiting the lectotype of Biscutella boetica (Brassicaceae) - Vicente, Alicia; Alonso, Mª Ángeles; Gautier, Laurent; Crespo, Manuel B. (Phytotaxa, 2016)
Biscutella boetica Boiss. & Reut. in Boissier (1854: 42) was described from material collected in southern Spain (“Hab. in sterilibus Boeticae circâ Malaga, Cartagena, etc. etc.”) by P.E. Boissier. The protologue includes a detailed description with diagnostic differences with regard to other annual congeners, such as B. microcarpa Candolle (1811: 298) (currently synonymised to B. lyrata Linnaeus 1771: 254), B. didyma Linnaeus (1753: 653), B. apula Linnaeus (1771: 254) nom. illeg., or B. depressa Willdenow (1809: 673) (the latter two sometimes treated as synonyms, varieties or even subspecies of B. didyma; cf. Vicente et al. 2015). The description also cites in synonymy the name B. apula var. [α] megacarpaea Boissier (1839: 55), which he had previously applied to collections from Málaga, Estepona and Ronda (southern Spain).